New Geographies of Abstract Art in Postwar Latin America - Alvarez, Mariola V. (Milton)
1 online resource (269 pages)
Keywords: This edited volume examines the history of abstract art across Latin America after 1945. This form of art grew in popularity across the Americas in the postwar period, often serving to affirm a sense of being modern and the right of Latin America to assume the leading role Europe had played before World War II. Latin American artists practiced gestural and geometric abstraction, though the history of art has favored the latter. Recent scholarship, for instance, has focused on geometric abstraction from Argentina, Brazil, and Venezuela. The book aims to expand the map and consider this phenomenon as it developed in neglected regions such as Central America and the Andes, investigatinghow this style came to stand in for Latin American contemporary art.